Evaluation of Different Techniques in Recovering of Oocytes and Storage Duration of Ovaries on the Quality and Quantity of Bovine in Vitro Maturation - Zaituni Udin; Masrizal Masrizal; Hendri Hendri; Syafri Nanda (Buletin Peternakan, 2020)
This study aimed to evaluate different recovery techniques of oocytes and the duration time between ovary collection and processing in the laboratory on the quality and quantity of Simmental cross bovine oocytes in vitro maturation. A total of 75 bovine ovaries were divided into three groups. Experiment-1;  the storage duration of ovaries were 6, 9 and 12 h. Experiment -2;  the techniques for oocytes recovery were slicing, aspiration and slicing + aspiration. The ovaries were collected from slaughterhouse and kept in saline solution during transportation to laboratory. A total of 136 oocytes were used for experiment-1, and 246 oocytes for experiment-2. This study found that the number and quality of oocytes were significantly different (P<0.05) as the effect of storage time. The average number of oocytes were 15.90±2.48; 17.10±1.38 and 13.60±3.00, in 6 h; 9 h and 12 h of storage time, respectively. The techniques of oocytes collection significantly (P<0.05) affect the quantity of oocytes but no significant (P>0.05) on oocytes quality. The average of oocytes of groups slicing, aspiration and slicing plus aspiration were 14.66±2.09; 9.46±2.99 and 16.40±6.86, respectively. Both experiment was significant effect (P<0.05) on immaturation rate of bovine. Conclusion of this study the storage time of ovaries was suitable in 9 h and the technique of oocytes collection was in slicing plus aspiration.